PRODUCTION AND RISKS ANALYSIS OF BROILER CHICKEN BREEDERS; CASE STUDY OF INDEPENDENT FARMERS IN LAWE BULAN DISTRICT, SOUTHEAST ACEH DISTRICT - Unchu Maiwanda; Sri Fajar Ayu; Nevy Diana Hanafi (RADJA PUBLIKA, 2024)
The relatively high cost of commercial feed can affect the production of broiler chickens so that it can affect production risks, prices and income. The aim of this research is to analyze the production of broiler chicken breeders and analyze the production risks faced by independent broiler chicken breeders in Lawe Bulan District, Southeast Aceh Regency, because there are still some farmers who have stopped running broiler chicken farming businesses because they experience high risks. This research was conducted in Lawe Bulan District, Southeast Aceh Regency. Data collection methods usedThere is this research, namely Observation, namely data collection carried out through direct observation of the conditions of the research location, as well as various breeder activities in carrying out the broiler chicken farming business such as preparing the cage, procuring and inserting seeds into the cage, raising chickens and harvesting and marketing. Interviews are data collection carried out through direct interviews with 30 respondents. The results of the research show that the broiler chicken farming business in Lawe Bulan District, Southeast Aceh Regency is profitable for livestock that is feasible to continue and has low risk.